Trypanosomatids in dogs belonging to individuals with chronic Chagas’ disease living in Botucatu town and surrounding region, São Paulo State, Brazil - Lucheis, S. B. [UNESP]; Da Silva, A. V.; Araújo Jr, J. P. [UNESP]; Langoni, H. [UNESP]; Meira, D. A. [UNESP]; Marcondes-machado, J. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Among domestic animals, dogs are considered to be the major reservoirs of trypanosomatids and, due to their proximity to man, the presence of these parasites in dogs is an alert to actions aiming at triatomine control. Fifty dogs (26 males and 24 females), aged from 2 months to 15 years, belonging to 30 chronic Chagas’ disease individuals from 15 different municipalities in the western region of São Paulo State, Brazil, were subjected to blood collection for the following tests: artificial xenodiagnosis, blood culture, and Polymerase Chain Reaction (PCR). Forty-three (86%) out of 50 dogs were positive to at least one of the tests performed; 34 (68%) were positive to xenodiagnosis, 30 (60%) to blood culture, and 25 (50%) to PCR for T. cruzi and/or T. rangeli. Although triatomines were not detected during the intra and peridomiciliary inspections in the dog owners’ residences, the results obtained demonstrate that there is a transmission cycle whereby triatomine vector may be participating in the infection epidemiological chain.
Keywords: Trypanosoma cruzi; T. rangeli; dog; xenodiagnosis; blood culture; polymerase chain reaction